PENGUATAN HAFALAN JUZ AMMA MENGGUNAKAN METODE MAKE A MATCH DI TAMAN BELAJAR BIDAYATUL HIDAYAH - Rizha Alfianita; Rayno Dwi Adityo; Elvina Meliana; Intan Hafidhatun Nisaa; Masrizal Masrizal; Ziyana Shofa Al Arifin (Al-Ihsan: Journal of Community Development in Islamic Studies, 2023)
Education at TPQ focuses on fostering students so they can read the Quran properly and correctly and teach basic religious knowledge such as procedures for ablution and prayer, readings in prayer, and daily prayer. Memorizing juz amma is also one of the materials that must be available, but sometimes students tend to easily forget what they have memorized because of the lack of murajaah at home. The purpose of this community service is to introduce the make-a-match learning method to strengthen students' memorization. During the learning process using the make a match method, students are very enthusiastic because they can play while learning, learning is also more lively so that learning can run smoothly and be easily accepted. Thus, students' memorization will be embedded in their memory because they have been trained to arrange pieces of verse into a coherent surah.